2006
DOI: 10.3727/000000006783981008
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Epigenetic Alterations of LTF at 3p21.3 in Nasopharyngeal Carcinoma

Abstract: To investigate the roles of lactotransferrin gene (LTF, also referred to as the lactoferrin gene, LF), located at 3p21.3 within the common minimal deletion region, in the pathogenesis of nasopharyngeal carcinoma (NPC), we first detected its expression level in 33 primary NPC tissues and 15 chronic nasopharyngitis tissues. Absent expression or downregulation of LTF were observed in 76% (25 of 33) of primary NPC tissues. We further found that 25% (5 of 20) of NPC specimens had loss of heterozygosity (LOH) at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 0 publications
3
30
0
Order By: Relevance
“…In addition, the LTF gene is inactivated by genetic and epigenetic mechanisms in lung cancer (24). Previous studies have also indicated that LTF may have a direct effect on tumor cell growth, as suggested by the fact that LTF and an LTF splice variant are downregulated or absent in certain types of cancer (25)(26)(27)(28). The results of the present study indicate that LTF may also serve as an important tumor suppressor gene in GC.…”
Section: Discussionsupporting
confidence: 58%
“…In addition, the LTF gene is inactivated by genetic and epigenetic mechanisms in lung cancer (24). Previous studies have also indicated that LTF may have a direct effect on tumor cell growth, as suggested by the fact that LTF and an LTF splice variant are downregulated or absent in certain types of cancer (25)(26)(27)(28). The results of the present study indicate that LTF may also serve as an important tumor suppressor gene in GC.…”
Section: Discussionsupporting
confidence: 58%
“…9 LTF may act as a tumor suppressor to downregulate the progression and metastasis of NPC. As hypermethylation in the LTF promoter region was observed in a large number of primary NPC tissues, 37 inactivation of LTF gene expression in NPC is likely to be mediated by promoter hypermethylation and histone deacetylation of the tumor suppressor gene. 8,30 Notably, LTF expression was detected in several advanced stage NPCs after metastasis to local lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…Nair et al [33] found that SEMA3B expression in neuroblastoma cells increased significantly after treatment with another de-methylation agent, 5-aza-2-deoxycytidylate. However, Yi et al [34] found that 100% of nasopharyngeal carcinoma samples and 73.3% of chronic nasopharyngitis tissue tested showed hypermethylation of the SEMA3B promoter, which suggests that hypermethylation of the SEMA3B promoter is related to inflammation, aging or other physiological and pathological conditions; that are un elated to the pathogenesis and development of nasopharyngeal carcinoma. Studies by Nair et al [33] also indicated that cells without methylation of the SEMA3B promoter have low expression levels of SEMA3B, suggesting that methylation is not necessary for the inactivation of SEMA3B.…”
Section: Inactivation Of Sema3b Tumor Suppression and The Relationshimentioning
confidence: 99%
“…Riquelme et al [35] [34] reported that the total LOH frequency of SEMA3B in patients with nasopharyngeal carcinomas was 45%, and the expression level of the SEMA3B gene was negatively correlated with LOH. However, Osada et al [36] did not find a correlation between LOH and mRNA expression deficiency of SEMA3B in ovarian epithelial samples.…”
Section: Inactivation Of Sema3b Tumor Suppression and The Relationshimentioning
confidence: 99%